A measure of core inflation in the UK - Andrade, Isabel C. (2010)
We develop a measure of core inflation in the UK over the period January1987 - December 1998, following the work of Bryan and Cecchetti (1996),Bryan, Cecchetti and Wiggins (1997) and Roger (1997). Disaggregation is into85 price categories. Given the high kurtosis of the price change distribution over this period, a trimmed mean is a more robust estimator of core inflation than other published measures such as the RPIX widely used in the UK, in particular by the Bank of England when targeting inflation. We discuss the relative advantages of our measure of core inflation, with emphasis on the determination of an optimal trimming point and on the analysis of the products whose price changes are excluded from our measure in each time period. The resulting measure appears well behaved, but differs noticeably from a number of published measures.